Green Purification of Mitragynine from Kratom Leaves (Mitragyna speciosa) through Solvent Variation in Acid-Base Extraction - Meiny Suzery; Bambang Cahyono; Saniya Almasa Taqiya; Safira Zikria (Universitas Diponegoro, 2026)
Kratom (Mitragyna speciosa) is a major natural source of mitragynine, an indole alkaloid with potentialas an alternative analgesic to opioids. However, conventional chromatographic purification methods arecostly and generate large volumes of solvent waste, making them less compatible with green chemistryprinciples. This study aimed to develop a non-chromatographic purification method using acid–base liquid–liquid extraction (ABLLE) by varying the partition solvent. Kratom leaves were extracted with ethanol andmethanol, and the alkaloids were subsequently separated through acidification, basification, and liquid–liquid partitioning using ethyl acetate and dichloromethane. Total alkaloid content (TAC) was determinedby UV–Vis spectrophotometry based on the bromocresol green (BCG) reaction, while mitragynine purity wasquantified using high-performance liquid chromatography with ultraviolet detection (HPLC-UV). The resultsshowed that the ethanol–dichloromethane system produced the alkaloid fraction with the highestmitragynine purity, reaching 39.09%, whereas the ethanol–ethyl acetate system yielded a purity of 27.47%.Both systems demonstrated a process efficiency of approximately 19%, with lower solvent consumption andreduced process waste compared with column chromatography. These findings indicate that acid–baseliquid–liquid extraction has the potential to serve as a simpler, scalable, and more sustainable approach formitragynine purification, thereby